The Prevalence of Asthma and Respiratory Symptoms among Cross-Country Skiers in Early Adolescence - E. Lennelöv; T. Irewall; E. Naumburg; A. Lindberg; N. Stenfors (Canadian Respiratory Journal)
Objective. To determine the prevalence of asthma and respiratory symptoms among Swedish cross-country skiers in early adolescence in comparison to a population-based reference group of similar ages. Methods. A postal questionnaire on asthma, asthma medication, allergy, respiratory symptoms, and physical activity was distributed to Swedish competitive cross-country skiers aged 12–15 years (n = 331) and a population-based reference group (n = 1000). The level of asthma control was measured by the Asthma Control Test. Results. The response rate was 27% (n = 87) among skiers and 29% (n = 292) in the reference group. The prevalence of self-reported asthma (physician-diagnosed asthma and use of asthma medication in the last 12 months) and the prevalence of reported wheezing during the last 12 months were 23% and 25%, respectively, among skiers, which were significantly higher than the values reported in the reference group (12% and 14%). Skiers exercised more hours/week than the reference group. Among adolescents with self-reported asthma, neither the usage of asthma medications nor the level of asthma control according to the Asthma Control Test differed between skiers and the reference group. Conclusions. Adolescent competitive cross-country skiers have an increased prevalence of respiratory symptoms and asthma compared to nonskiers.